Aplikasi Sistem Pencarian Halte BRT Terdekat Kota Semarang Menggunakan Metode A* Berbasis Android - Abimanyu Cahya Pramudhita; Muljono Muljono (Ikatan Ahli Informatika Indonesia (IAII), 2018)
BRT (Bus Rapid Transit) is one of public transportation that can be used in Semarang City. This bus is operated to break down the congestion in Semarang city which is increasing. This paper aims to make the application of the bus stop search system closest and is expected to facilitate the people of Semarang city in the use of BRT (Bus Rapid Transit). A* Algorithm, This algorithm is a Best First Search algorithm that combines Uniform Cost Search and Greedy Best-First Search. Where the Price considered f(n) is derived from the actual price g(n) plus the approximate price h(n). The created application provides the nearest stop information by using the A* method. From the calculations performed using the A* method and conducted 20 experiments at different locations, the A* method has 100% accuracy in determining the nearest up and down stops, if in an accurate Global Positioning System.